Prevalence of non-strongyle gastrointestinal parasites of horses in Riyadh region of Saudi Arabia - AL Anazi, Abdullah D. (2011)
This study aimed to provide recent data on the occurrence of non-strongyle intestinal parasite infestation in horses in the Riyadh region of Saudi Arabia as a basis for developing parasite control strategies. We conducted necropsy for 45 horses from September 2006 to November 2007 in the Riyadh region, Saudi Arabia. 39 out of 45 horses were infected with intestinal parasites with an infestation rate of 86.6%. Infestations with seven nematode species and two species of Gasterophilus larva were found. The most prevalent parasites were Strongyloides westeri (64.4%) and Parascaris equorum (28.8%) followed by Habronema muscae (22.2%). Trichostrongylus axei and Oxyuris equi were less common at (11.1%) and (8.8%), respectively. Habronema megastoma and Setaria equine were found in two horses only (4.4%). Gasterophilus intestinalis larvae were recovered from 39 horses (86.6%) and Gasterophilus nasalis larvae were found in 17 horses (37.7%). Season had a significant effect on the prevalence of P. equorum and G. nasalis, while age of horses had a significant effect only on the prevalence of P. equorum. The husbandry in Saudi Arabia appears to be conductive to parasites transmitted in stables or by insects rather than in pasture.